Analisis Mutu Produk Sweet Bread Untuk Hidangan Breakfast di Fairfield By Marriott Surabaya - Ayu Sekar Nurani; Niken Purwidiani; Ita Fatkhur Romadhoni; Lucia Tri Pangesthi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted at Fairfield by Marriott Surabaya in February – June 2024. The focus of this research was to determine the quality of sweet bread. This research uses theories from experts who study sweet bread, sweet bread quality, and organoleptic tests. The method used in this research is a quantitative method with a descriptive approach, using observation techniques with organoleptic tests in terms of volume, crust color, crust texture, pores, moisture, shape, aroma, taste, and level of preference and documentation in the form of a standard recipe. , the process of making and serving sweet bread. The data collection technique used was organoleptic test sheets and documentation, data analysis used was percentage. The final results of this research show that product quality in terms of volume, 60% of panelists chose to expand 3 times. crust color, as many as 54% of panelists chose brownish yellow, crust texture as many as 60% of panelists chose thin & dry, pores, as many as 40% of panelists chose quite small and uneven, humidity as much as 80% of panelists chose quite moist, the highest form of assessment in the roti boy variant was 73% of the panelists, the highest taste of the roti boy variant was 73% of the panelists, the highest aroma of the shredded variant was 77% of the panelists, and the highest level of preference for the cheese variant was 50% of the panelists. Improvements can be made through the quality of ingredients, manufacturing processes and storage of sweet bread.